BISNIS DIGITAL YANG BERKAH: MEMBINGKAI ULANG EKONOMI ISLAM DI ERA TEKNOLOGI MELALUI PENDEKATAN MAQASID SYARIAH - Aisiyah Nur Afifah; Mira Ustanti (Jurnal Ekonomi Syariah Darussalam, 2026)
Digital transformation has accelerated the development of the Islamic economy through innovations such as Islamic fintech, halal e-commerce, and the digitalization of zakat, infaq, sadaqah, and waqf (ZISWAF). However, these developments have also given rise to challenges, including unclear digital contracts. This study aims to analyze the implementation of Maqasid Shariah in digital business and to formulate a conceptual model of a digital business ecosystem oriented toward public welfare (maslahah). The study employs a qualitative approach by examining academic literature, DSN-MUI fatwas, statutory regulations, and official documents. Data were analyzed using content analysis, conceptual analysis, and synthesis. The findings indicate that Maqasid Shariah serves as a strategic foundation for developing a digital business ecosystem that ensures Sharia compliance, protection of rights, transparency, economic justice, and sustainability. Furthermore, this study proposes a conceptual model of a Maqasid Shariah based digital business ecosystem built upon four main pillars: Sharia compliance, protection and transparency, inclusion and economic justice, and sustainability to promote public welfare within the digital Islamic economy. Keywords: Digital Business, Maqashid Shariah